Examining Relationship-Level Predictors of Individual-Level Health in Long Distance Relationships. (July 2022) - Du Bois, Steve N.; Woodward, Honor; Manser, Kelly; Saigal, Seema; Santic, Frane; Tully, Timothy; Sher, Tamara Goldman
Long distance relationships (LDR) are increasingly common, particularly among postsecondary students. The geographic separation inherent in LDR, and related relationship factors, may have implications for the health of individuals in LDR. However, little current work examines these potential associations. The current study examined associations between relationship-level predictors (satisfaction, stress, maintenance) and individual-level health (e.g., anxiety, depression, sleep disturbance, fatigue) and health behaviors (e.g., alcohol and cigarette use, sex) in LDR. Participants ( N   =  100) were postsecondary students and romantic partners of postsecondary students, recruited from October 2018–June 2019, who completed an online survey on relationships and health. Here, we report sample characteristics; correlations between key study variables; and, results of stepwise hierarchical regressions testing whether relationship-level variables predicted individual-level health. Results indicated that relationship satisfaction and relationship stress predicted self-reported health in multiple domains, in the expected directions; but, neither relationship satisfaction nor relationship stress predicted health behaviors. Relationship maintenance predicted neither self-reported health nor health behaviors. Overall, some, but not all, relationship-level variables influenced some, but not all, individual-level health variables among postsecondary students and partners of postsecondary students in LDR. Future work can clarify relationship-level predictors of individual-level health behaviors in postsecondary students, among whom LDR are prevalent.